In spies we trust the story of Western intelligence - Jeffreys-Jones, Rhodri (Oxford Oxford University Press, 2013)
"In Spies We Trust reveals the full story of the Anglo-American intelligence relationship - ranging from the deceits of World War I to the mendacities of 9/11 - for the first time. Why did we ever start trusting spies? It all started a hundred years ago. First we put our faith in them to help win wars, then we turned against the bloodshed and expense, and asked our spies instead to deliver peace and security. By the end of World War II, Britain and America were cooperating effectively to that end. At its peak in the 1940s and 1950s, the 'special intelligence relationship' contributed to national and international security in what was an Anglo-American century" -- Provided by publisher.
The separate origins of American and British intelligence -- Great war origins of the Anglo-American intelligence partnership -- Implications of the Zimmermann telegram -- The special intelligence relationship in the Second World War -- CIA: the new model agency -- Surviving mistrust: Cold War intelligence episodes -- Vietnam, Guyana, Ramparts: trust in decline -- An American gift: government in the sunshine -- The distant cousin: America goes its own way -- Europol -- The quest for European intelligence -- Beyond the old west.
Includes bibliographical references (page 263-280) and index.
Keywords: Espionage, British -- History -- 20th century; Espionage, British -- History -- 21st century; Espionage, American -- History -- 20th century; Espionage, American -- History -- 21st century; Great Britain -- Foreign relations -- United States; United States -- Foreign relations -- Great Britain; Great Britain -- Foreign relations -- 20th century; Great Britain -- Foreign relations -- 21st century; United States -- Foreign relations -- 20th century; United States -- Foreign relations -- 21st century